Association Between Hospital Participation in Medicare Shared Savings Program Accountable Care Organizations and Readmission Following Major Surgery. Issue 5 (May 2019) - Borza, Tudor; Oerline, Mary K.; Skolarus, Ted A.; Norton, Edward C.; Dimick, Justin B.; Jacobs, Bruce L.; Herrel, Lindsey A.; Ellimoottil, Chad; Hollingsworth, John M.; Ryan, Andrew M.; Miller, David C.; Shahinian, Vahakn B.; et al.
Abstract : Objective: To evaluate the effect of Medicare Shared Savings Program accountable care organizations (ACOs) on hospital readmission after common surgical procedures. Summary Background Data: Hospital readmissions following surgery lead to worse patient outcomes and wasteful spending. ACOs, and their associated hospitals, have strong incentives to reduce readmissions from 2 distinct Centers for Medicare and Medicaid Services policies. Methods: We performed a retrospective cohort study using a 20% national Medicare sample to identify beneficiaries undergoing 1 of 7 common surgical procedures—abdominal aortic aneurysm repair, colectomy, cystectomy, prostatectomy, lung resection, total knee arthroplasty, and total hip arthroplasty—between 2010 and 2014. The primary outcome was 30-day risk-adjusted readmission rate. We performed difference-in-differences analyses using multilevel logistic regression models to quantify the effect of hospital ACO affiliation on readmissions following these procedures. Results: Patients underwent a procedure at one of 2974 hospitals, of which 389 were ACO affiliated. The 30-day risk-adjusted readmission rate decreased from 8.4% (95% CI, 8.1–8.7%) to 7.0% (95% CI, 6.7–7.3%) for ACO affiliated hospitals ( P < 0.001) and from 7.9% (95% CI, 7.8–8.0%) to 7.1% (95% CI, 6.9–7.2%) for non-ACO hospitals ( P < 0.001). The difference-in-differences of the 2 trends demonstrated an additional 0.52% (95% CI, 0.97–0.078%) absolute reduction in readmissions at ACO hospitals ( P = 0.021), which would translate to 4410 hospitalizations avoided. Conclusion: Readmissions following common procedures decreased significantly from 2010 to 2014. Hospital affiliation with Shared Savings ACOs was associated with significant additional reductions in readmissions. This emphasis on readmission reduction is 1 mechanism through which ACOs improve value in a surgical population. Abstract : Supplemental Digital Content is available in the text